The relationship between Dividend Payout ratio and Capital Structure of companies quoted at the Nairobi Securities Exchange, Kenya in the industrial and allied sector - Sang, William; Shisia, Adam; Gesimba, Paul; Kilonzo, Timothy (International Journal of Economics, 2015)
The existing literature on optimal dividend policy and capital structure is voluminous and has continuously evolved over the last five decades. The objective of this study was to establish the relationship between the dividend payout ratio and capital structure of companies listed at the NSE. This study relied on secondary data. The study sampled 16 companies in the industrial and allied sector listed at the NSE. Regression analysis was used to analyze the data and find out whether there exists a relationship between dividend payout ratio and capital structure. The study found out that there is a significant relationship between dividend payout ratio and capital structure. The findings revealed that there is a strong inverse relationship between leverage and dividend payout ratio while there is a weak inverse relationship between retained earnings and dividend payout ratio. The study concludes that retained earnings and leverage negatively affects dividend payout ratio. Based on these results, the study recommends company’s management education, as they need to understand the factors that lead to increase or decrease in the company’s dividend payout ratio.
Keywords: Nairobi Securities Exchange; Dividend Per Share; Pay Out Ratio; Capital Structure